Peacekeeping without Conflict Resolution: The Kashmir Dispute - Alam, G. M. Shahidul (Tufts Archival Research Center, 2005)
Volume 6, Issue 1. Winter Although in the aftermath of World War II the peacekeeping function of the United Nations was viewed as likely to promote the pacific development of disputes, three decades later it is clear that merely separating the combat forces of contending states does not bring the political resolution of conflict any closer. The United Nations has maintained a peacekeeping force in the troubled Kashmir region between Pakistan and India for more than thirty years. In this article, Shahidul Alam uses this long-standing dispute to illustrate the problems encountered by United Nations in promoting the resolution of international disputes. He concludes that the United Nations' use of peacekeeping forces to police cease-fires may actually prolong, rather than speed, the ultimate resolution of conflict.